Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations your face. Electric light is steady and softly brilliant, especially if an opal bulb or a light shade is used to protect the eyes from glare. Flickering light, sitting in one's own light, and a dim light are all bad for the eyesight, and to be avoided. [illustration] Use your towel and handkerchief yourself only. Eyes are delicate and valuable possessions, and they are best left alone, only taking reasonable care to treat them properly. Clear eyes can give Beauty to an otherwise plain face, and their transparent brightness depends on the health of the whole body, inside and out. If they are heavy and dull with "blacks" under them, it is high time you attended to bowels, or diet, or gave up too many dances and "pictures," with their late hours and stale used-up air. Should your eyes cause you to wear a worried look, to frown or blink, or to twitch your face, they need the skilled attention of an oculist. Never go to an unqualified person, nor buy a pair of spectacles chosen from a heap by yourself. You must not think they will get better by themselves in time. They may seem to improve, but that is because the eyes adjust themselves to bad conditions which should be remedied before the delicate organs are permanently injured. Headaches are an early sign of eye strain, and "bilious attacks," too, may arise from the same cause. If your eyes are inflamed you should never rub them; and at all times flannels and towels and handkerchiefs should be clean and used by no one but yourself. Should you be advised to wear glasses [illustration] 12 177/5/8/4